Dynamic interactions of commodities and policy uncertainty : a VARX-ADCC-EGARCH approach - Kallio, Anssi (2023)
In this study, I focused on three essential food staples: wheat, corn, and rice. Unfortunately, food prices are unstable, which can cause troubles in different economies in different economic cycles. As price stability is vital for so many, this research sought ways of decreasing price instability. Financial models and analysis have developed new accounting methods for economic policy uncertainty. The study used the VARX-ADCC-EGARCH model to investigate the return and volatility relationships between the selected assets. The model included the uncertainty indexes as exogenous variables and acting as shocks outside the system. The primary research was done on daily data to see the changes and evolution of the relationship and the risks between the variables. A simple ARX model was used to analyze the impact of the policy uncertainty on wheat, corn, and rice. Because the VARX-ADCC-EGARCH model gave conditional covariances and conditional variances of the assets as results, these results were used to build a minimum variance portfolio. The results revealed that the S&P 500 CI leads the returns on food staples, and the copper and gold futures influence the returns of foods. Interestingly, corn interactions are overall more frequent than wheat, and silver futures returns influence wheat, but corn and rice influence silver futures. 21-day rolling average portfolios were all long positions on S&P 500 CI, but other than that, the optimal portfolios varied a lot from each other from period to period and reflected the changing risks and interactions between the selected assets.